THE EXPRESSION OF Hsa-miR-21-5p AS MINIMAL INVASIVE MARKER TO ADJUVANT CHEMOTHERAPY IN BREAST CANCER PATIENTS - Dewi Safitri Tanjung; MS. Fitria; AI. Kartika; D. Rakhmina; SL. Anwar; R. Oktriani; . Irianiwati; SM. Harjana; T. Aryandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractBreast cancer remains the leading cause of death among women, and there is a need to develop minimally invasive marker. In our previous study based on clinicopathologic in pre-chemotherapy patients showed miR-21 was upregulated 1.32 times higher at advanced stage compared with early stage. Therefore the matched patients for post-chemotherapy samples were used. The aim of this research is to examine the expression of miR-21 as potential marker to adjuvant chemotherapy in breast cancer patients. The samples were taken by using cross sectional method with total 39 blood plasma samples from breast cancer patients in adjuvant chemotherapy and 12 healthy control samples. Plasma was obtained from blood samples and then RNA isolated were performed. Total RNA was reverse transcribed using cDNA synthesis. The expression of miR-21 was then analyzed using specific primer for miR-21 and miR-16 as the reference gene. Livak Method was used to calculate the expression level in each group. The result showed that there is significant downregulated expression of miR-21 in postchemotherapy 2.61 fold compared with pre-chemotherapy (p<0.05). The expression of miR-21 upregulated 2.2 folds (p<0.05) in pre-chemotherapy compared with healthy control, while in post-chemotherapy compared with healthy control, the expression of miR-21 was 0.8 fold (p<0.05). In conclusion, Hsa-miR-21-5p can be used as marker for adjuvant chemotherapy response in breast cancer because there is significant different expression between prechemotherapy, post-chemotherapy and healthy control. The continuation research in the near future for detecting the expression of tumor suppressor protein regulated by miR-21 is needed.Keywords: breast cancer, adjuvant chemotherapy, miR-21, minimal invasive marker